Figure 16 from: Saarela JM, Sokoloff PC, Gillespie LJ, Bull RD, Bennett BA, Ponomarenko S (2020) Vascular plants of Victoria Island (Northwest Territories and Nunavut, Canada): a specimen-based study of an Arctic flora. PhytoKeys 141: 1-330. https://doi.org/10.3897/phytokeys.141.48810 - Saarela, Jeffery M.; Sokoloff, Paul C.; Gillespie, Lynn J.; Bull, Roger D.; Bennett, Bruce A.; Ponomarenko, Serguei (Zenodo, 2022)
Figure 16 ACarex myosuroides habit BCarex myosuroides habitat CCarex petricosa subsp. petricosa habit, Gillespie et al. 9657DCarex petricosa subsp. petricosa habitat, Gillespie et al. 9657. Photos A, B by B.A. Bennett and C, D by J.M. Saarela.